Comparison Between Usability and User Acceptance Testing on Educational Game Assessment - Vanesha, Nellya Anggun; Rizky, Rizky; Purwanto, Agus (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
User Acceptance Testing (UAT) and Usability Testing are two methods commonly used in evaluating software or systems. UAT is concerned with overall system acceptance, while Usability Testing is specifically aimed at assessing the user's experience in interacting with the product. These two testing methods play an important role in ensuring the quality and user satisfaction of software and systems. Including being used to evaluate the Little Panda's Forest Animals game against 106 respondents consisting of two different campuses. The purpose of this research is to see the comparison between Usability Testing and User Acceptance Testing. With the research stages of literature review, questionnaire creation, data collection, data processing, and conclusions. The results of data processing show that there are differences in results where Usability Testing gets a lower score than User Acceptance Testing. Usability Testing results received an assessment range of 65 - 84 with the Usability statement being acceptable to users, while User Acceptance Testing received a range of 81% - 100% with the score interpretation criteria being very good.